Abuse of elderly in Sweden 1987 - Tornstam, Lars (Uppsala University, 1990)
During October 1987 the national Swedish institute of statistics made 943 telephone interviews about elder abuse with men and women between 18 and 74 years of age. In Denmark the the Danish national institute of statistics made the same kind of interviews with 1.535 men and women, 16 years and over. The representative samples were asked whether they knew about specific cases, in the surroundings or among the acquaintances, where retired people in their homes had been battered, threatened, economically exploited, the victims of theft or severely neglected. In both Sweden and Denmark 8 percent of the respondents report knowledge of such a case, where the abuse took place within the last 12 months. The perpetrators were unknown persons, family members and various kinds of caring staff (home helpers etc). In Sweden the 'staff' category was mentioned as perpetrator in 20 percent of the specific cases while in Denmark only 6 percent. This difference might be due to the fact that a larger proportion of the home helpers in Denmark is formally trained. A conclusion is that the 'staff' category can not be excluded when studying abuse in the 'families' of the elderly.

During October 1987 the national Swedish institute of statistics made 943 telephone interviews about elder abuse with men and women between 18 and 74 years of age. In Denmark the the Danish national institute of statistics made the same kind of interviews with 1.535 men and women, 16 years and over. The representative samples were asked whether they knew about specific cases, in the surroundings or among the acquaintances, where retired people in their homes had been battered, threatened, economically exploited, the victims of theft or severely neglected. In both Sweden and Denmark 8 percent of the respondents report knowledge of such a case, where the abuse took place within the last 12 months. The perpetrators were unknown persons, family members and various kinds of caring staff (home helpers etc). In Sweden the 'staff' category was mentioned as perpetrator in 20 percent of the specific cases while in Denmark only 6 percent. This difference might be due to the fact that a larger proportion of the home helpers in Denmark is formally trained. A conclusion is that the 'staff' category can not be excluded when studying abuse in the 'families' of the elderly.
Misshandel av äldre i Sverige 1987
Keywords: care of the elderly; äldreomsorg; Aged; Äldre; old age; ålderdom; theft; stöld; crime victims; brottsoffer; witness intimidation; vittneshot; elder abuse; äldremisshandel; disadvantaged groups; utsatta grupper; assault; våld; Crime and law enforcement; Kriminalitet och rättstillämpning; Elderly; Äldre; Social conditions and indicators; Sociala förhållanden och indikatorer; Social Sciences; Samhällsvetenskap; Sociology; Sociologi